A Method of Steganography – P Message With Q Coefficient (SPMQC) - Zeinab Famili; Karim Faez; Abbas Fadavi (Institute of Advanced Engineering and Science, 2013)
In this paper, we are going to propose a method for Steganography- which is based on deceiving χ2 algorithm. Since the cover image coefficients and stego image coefficients histograms have significant differences for purposes of statistical properties, statistical analysis of χ2-test reveals the existence of hidden messages inside stego image. We are introducing an idea for hiding messages in the cover image. It causes that DCT (Discrete Cosine Transforms) coefficient histogram not to have remarkable modification before and after embedding message. As a result, identifying the hidden message inside an image is impossible for an eavesdropper through χ2 -test. In this paper, we are proposing a better method with developing this algorithm. In fact, the capacity and the security of embedding messages increase extremely.DOI:http://dx.doi.org/10.11591/ijece.v3i2.2011